Sensasi yang Mengikat di Dunia Virtual: Hubungan Sensation Seeking Terhadap Internet Gaming Disorder pada Remaja - Meilani Putri Marlin; Rahayu, Ananda Sri; Alifia Putri Fadilah Sati; Emilya Dwinata; Rahmatul Ulfa; Sabilla Sistazha; Sakinatun Hasanah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
One of the popular entertainments in Indonesia, especially among teenagers, is online games. As a result, many teenagers undergo therapy at RSJ because they are addicted to online games, one of which is caused by the seeking sensation that individuals feel when playing online games. This research was conducted with the aim of seeing how sensation seeking relates to internet gaming disorder in adolescents. Researchers use quantitative research methods with correlational methods. The population in the study were teenagers in West Sumatra who played online games and were aged 12-21 years. The sampling technique in this research is accidental sampling or defined as anyone who meets the researcher by chance. Data was taken using the sensation seeking scale and online games. Data analysis in this research uses the product moment correlation coefficient and r-square value. The results of this research are that there is a significant positive relationship of r=0.236 and it is a weak degree of relationship